Storm impacts along European coastlines. Part 2: lessons learned from the MICORE project - Ciavola, Paolo (2018)
This paper describes the MICORE approach to quantify for nine field sites the crucial storm related physical hazards (hydrodynamic as well as morphodynamic) in support of early warning efforts and emergency response. As a first step historical storms that had a significant morphological impact on a representative number of sensitive European coastal stretches were reviewed and analysed in order to understand storm related morphological changes and how often they occur around Europe. Next, an on-line storm prediction system was set up to enable prediction of storm related hydro- and morphodynamic impacts. The system makes use of existing offthe- shelf models as well as a new open-source morphological model. To validate the models at least one year of fieldwork was done at nine pilot sites. The data was safeguarded and stored for future use in an open database that conforms to the OpenEarth protocols. To translate quantitative model results to useful information for Civil Protection agencies the Frame of Reference approach (Van Koningsveld et al., 2005, 2007) was used to derive Storm Impact Indicators (SIIs) for relevant decision makers. The acquired knowledge is expected to be directly transferred to the civil society trough partnerships with end-users at the end of the MICORE project.